Trends in surgical approaches and adnexal surgeries during hysterectomies for benign diseases between 2015–2021 - Zhu, Xuejiao; Xi, Hongli; Li, Zhifang; Wang, Xinping (Frontiers in Surgery, 2023)
Background: Hysterectomy is a widely used surgical approach for benign gynaecological conditions, while there have been differences in the choice of surgical route in different regions recently. Aims: To estimate the recent temporal trends, this study collected the data of surgical approach and adnexal surgeries at the time of hysterectomy for benign disease in 2015-2021 at a single institute. Materials and Methods: We retrospectively analysed data from Xiangyang No.1 People's Hospital, Hubei University of Medicine in Xiangyang, China and identified 1828 women underwent hysterectomies for benign gynaecologic conditions performed with or without bilateral salpingectomy (BS), bilateral salpingo-oophorectomy (BSO) between January 2015 and December 2021. Results: There was an increase in trend in the performance of hysterectomy and hysterectomy with BS and there was a difference in the trends of concomitant adnexal surgery between AH, TLH and VH, especially in TLH with BS. Patient characteristics data demonstrated that the most frequent indication for hysterectomy were leiomyoma, especially in age of 45-65. The operative bleeding, operative time, length of hospital stays of patients undergoing TLH with BS, BSO were both the lowest among AH, TLH and VH. For benign diseases, the surgical approach changed markedly due to gradually increased proportions of patients choosing operations using minimally invasive techniques. The laparoscopic approach is becoming popular due to its ability to lower intraoperative blood loss and reduce hospitalization. Conclusions: We should emphasis on surgical training for TLH approach and to help gynaecologic surgeons provide their patients with the proposed added benefit of BS.